2018
DOI: 10.1111/cen.13747
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Bethesda categories III and IV thyroid nodules over 5 years and performance of the Afirma gene expression classifier: A single‐institution study

Abstract: Our 5-year review demonstrated that malignancy rates of B3 and B4 nodules showed year-to-year variability. We suggest that clinicians use a multi-year average of their institution's malignancy rates to optimally manage patients. Follow-up for GEC Benign cases thus far supports their indolent nature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 22 publications
0
23
1
Order By: Relevance
“…This is higher than the typically accepted rates reported in the literature of 6‐18% and 10‐40%, respectively . The frequency of indeterminate cytology as well as the malignancy rate for these nodules is known to vary by institution, and similar malignancy rates for nodules interpreted as atypia of undetermined significance/follicular lesion of undetermined significance have been reported . However, the overall higher than expected malignancy rates in nodules with indeterminate cytology in our study may limit the generalizability of our results to institutions where the malignancy rate for these nodules is lower.…”
Section: Discussioncontrasting
confidence: 72%
“…This is higher than the typically accepted rates reported in the literature of 6‐18% and 10‐40%, respectively . The frequency of indeterminate cytology as well as the malignancy rate for these nodules is known to vary by institution, and similar malignancy rates for nodules interpreted as atypia of undetermined significance/follicular lesion of undetermined significance have been reported . However, the overall higher than expected malignancy rates in nodules with indeterminate cytology in our study may limit the generalizability of our results to institutions where the malignancy rate for these nodules is lower.…”
Section: Discussioncontrasting
confidence: 72%
“…Subsequently, 28 real‐world clinical experience studies have cumulatively reported that only 13% of nodules with GEC benign results underwent surgical resection, a marked reduction compared with the historical treatment of patients with cytologically indeterminate thyroid nodules . In 26 of these studies, only 3% of nodules (50 of 1934 nodules) with GEC benign results were found to be malignant . Investigators who assessed GEC test performance only in operated cases with surgical histology systematically underestimated test specificity and NPV by excluding many unoperated GEC benign nodules that were very likely true‐negative results .…”
Section: Introductionmentioning
confidence: 99%
“…In the studies that did report these rates, results were highly variable, with a resection rate ranging from 17% to 100% with a malignancy rate in these nodules of 0% to 100%. 7,8,12,13,17,18,21,25,26,29 Of the 12 initially unresected nodules in our study, 9 (75%) had a repeat biopsy, of which only 1 had a “suspicious” GEC result. Therefore, it is prudent to consider all other clinical elements as well as patient preference when deciding how to manage a nodule with a “no result” reading.…”
Section: Discussionmentioning
confidence: 60%
“…This number is slightly lower than reported in the initial validation study 3 and at other institutions. 5-30 Our large population of high-risk patients leads to a high pretest probability of malignancy, which may have contributed to our lower negative predictive value. The prevalence of thyroid malignancy in patients with thyroid nodules with indeterminate cytology at our institution during this timeframe was 41%, thus lowering our negative predictive value.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation